Penggunaan aplikasi SRIKANDI (Sistem Informasi Kearsipan Dinamis Terintegrasi) dalam proses pengelolaan arsip di Sekretariat DPRD Kota Batu - Almira, Davina (Maliki Interdisciplinary Journal, 2024)
The use of the SRIKANDI application has been key in the digital transformation of many government institutions, including the Batu City DPRD Secretariat. This application provides an effective solution in archive management, enables document digitization, and increases efficiency and security in information storage and access. This research method uses a descriptive qualitative approach which includes observation, interviews, and documentation with resource persons from Batu City DPRD Secretariat employees. This research aims to find out how to use the SRIKANDI application in the archive management process at the Batu City DPRD Secretariat effectively and efficiently. The research results show that the use of the SRIKANDI application has brought a positive transformation in archive management and administration within the Batu City DPRD Secretariat. Digitization of these archives allows fast and easy access to documents, increasing employee efficiency and productivity. Meanwhile, the obstacle that often occurs is the lack of understanding of older employees regarding digital archive systems and internet networks that are sometimes down, which hinders the employee’s performance process.